Pelatihan dan Edukasi dalam Pengelolaan Lingkungan Fisik Rumah pada Pasien TB Paru di Wilayah Kerja Puskesmas Binanga: Training and Education in the Management of the Physical Home Environment for Pulmonary TB Patients in the Work Area of Binanga Health Center - Hasir Hasir; Nurhikmah Nurhikmah; Nurbaya Nurbaya (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Case Detection Rate (CDR) for TB cases in Mamuju Regency continues to increase every year. Data shows that in 2013 it was 110.63%, in 2014 it was 110.8%, in 2015 it was 147.02%, and 117.24% in 2016. In the incidence of pulmonary TB, the house is a factor that is widely studied because the house is thought to have a risk factor that influences the incidence of pulmonary TB in humans. This community service is carried out in the form of counseling and education about the management of the physical home environment for patients with pulmonary TB. This activity aimed to improve the abilities and skills of the trainees in managing the physical home environment for pulmonary TB patients. The extension method was in the form of lectures, discussions, and demonstrations of measuring light, humidity, and room temperature. A total of 25 participants were involved in this activity. The evaluation was carried out in the form of pre and post-test which contained 10 questions. Based on the post-test results, it was found that there was an increase in knowledge of 38.8%. Health workers need to provide regular assistance to families of TB patients so that there is a sustainable change in behavior related to the management of the household's physical environment. ABSTRAK Case Detection Rate (CDR) untuk kasus TB di Kabupaten Mamuju terus mengalami peningkatan setiap tahunnya. Data 2013 sebesar 110.63%, tahun 2014 tercacat 110.8%, tahun 2015 sebesar 147.02% dan 117.24% pada tahun 2016. Pada kejadian TB paru, rumah merupakan faktor yang banyak diteliti karena rumah diduga mempunyai faktor risiko yang berpengaruh besar terhadap kejadian TB paru pada manusia. Pengabdian masyarakat ini dilakukan dalam bentuk penyuluhan dan edukasi tentang pengelolaan lingkungan fisik rumah pada penderita TB Paru. Kegiatan ini bertujuan untuk meningkatkan kemampuan dan ketrampilan peserta pelatihan dalam pengelolaan lingkungan fisik rumah pada pasien TB Paru. Metode penyuluhan dalam bentuk ceramah, diskusi dan demonstrasi pengukuran cahaya, kelembaban udara dan suhu ruangan. Sebanyak 25 peserta terlibat dalam kegiatan ini. Evaluasi dilakukan dalam bentuk pre dan post-test yang berisi 10 pertanyaan. Berdasarkan hasil post-test diperoleh bahwa terjadi peningkatan pengetahuan sebanyak 38,8%. Petugas kesehatan perlu melakukan pendampingan secara rutin pada keluarga penderita TB agar terjadi perubahan perilaku yang berkelanjutan terkait pengelolaan lingkungan fisik rumah tangga.